2015
DOI: 10.1002/ange.201409894
|View full text |Cite
|
Sign up to set email alerts
|

Formal Asymmetric Catalytic Thiolation with a Bifunctional Catalyst at a Water–Oil Interface: Synthesis of Benzyl Thiols

Abstract: The enantioselective conjugated addition of tritylthiol to in situ generated ortho-quinone methides (o-QMs) is catalyzedb ya na cid-base bifunctional squaramide organocatalyst. The transformation proceeds with high yield (up to 99 %) and stereoselectivity (up to 97:3 e.r.)u sing water as solvent under mild conditions.T he catalyst system provides an ew strategy for the synthesis of optically active benzyl mercaptans.C ontrol experiments suggested that o-QMs are generated by the tertiary amine moiety of the squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 75 publications
2
3
0
Order By: Relevance
“…R f =0.46 (CHCl 3 ). The spectral characteristics of the compound are consistent with those presented in literature [22–24] …”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…R f =0.46 (CHCl 3 ). The spectral characteristics of the compound are consistent with those presented in literature [22–24] …”
Section: Methodssupporting
confidence: 89%
“…Aldehyde 6 was synthesized by formylation of sesamol ( 1 ) using the Duff reaction according to a convenient procedure. Variants of this synthesis for compound 6 have already been described in the literature and included refluxing the reaction mixture in TFA for 2–4 h showing 45–54 % yields [22–24] . In our modification to obtain the same product we used the more accessible and cheaper AcOH instead of TFA.…”
Section: Resultsmentioning
confidence: 99%
“…The calculations suggested that the C-C bond formation of the Duff reaction is an endothermic reaction with energies between 1.50 and 15.05 kcal mol −1 . The product ratio prediction using their relative product stabilities agreed well with the reported regioselectivities [61][62][63][64] and indicated that regioselectivity is under thermodynamic control. Additional studies implied that the R2 substitution was preferred for electron-withdrawing group substituted phenol, meanwhile the R6 substitution occurs when R is an electron-donating group.…”
Section: Case Studiessupporting
confidence: 75%
“…For example, Rueping developed a chiral BINOL‐based N ‐triflylphosphoramide‐catalyzed, enantioselective synthesis of special chromanes via [4+2] hetero‐Diels–Alder reactions between unactivated alkenes and in situ generated o ‐QMs . Li synthesized chiral benzyl thiols via the enantioselective conjugated addition of trityl thiol to in situ generated o ‐QMs, catalyzed by a bifunctional squaramide organocatalyst . Hayashi constructed the target triarylmethanes in highly optically enriched form through ortho ‐quinone methide intermediates which undergo Rh‐catalyzed asymmetric 1,4‐addition of the arylboron reagents .…”
Section: Figurementioning
confidence: 99%
“…The o ‐QM is generated in the organic phase with the production of TsH, which can protonate the basic nitrogen of the catalyst, and the resulting salt reacts with K 2 CO 3 , thereby regenerating the catalyst. On the other hand, the use of water as a second phase not only ensures mild conditions in the regeneration of the catalyst but also effectively realizes the spatial separation of the inorganic base from the organic phase to suppress the racemic background reaction, resulting an excellent activity and enantioselectivity. In addition, in the absence of an H‐bonding acceptor (OMe) at the 6 position of the o ‐QM fragment, there may exist two coordination modes, which led to poor enantioselectivities.…”
Section: Figurementioning
confidence: 99%